Indications for referrals to Chris Hani Baragwanath academic hospital gynaecological outpatients department - Rockson, Esther (My University, 2016)
Introduction Chis Hani Baragwanath Academic Hospital (CHBAH) is a tertiary (level 3) hospital located in Soweto, Johannesburg. There is no currently no fully functioning district hospital in Soweto. The CHBAH Gynaecological Outpatients Department (GOPD) is burdened by large numbers of patients with a case mix from all levels of care. Objective To describe the clinical characteristics of patients referred to Chris Hani Baragwanath Academic Hospital Gynaecological Outpatients Department and classify them according to levels of care, to assess the lower level case burden carried by the hospital. Methods A prospective cross sectional study was conducted over one week, and 200 participants were selected from the GOPD queue. The researcher interviewed each participant and studied their records to determine their demographic data, reasons for referral and presenting complaints. Upon the participant being seen by the on duty doctor, a provisional diagnosis was made and the appropriate level of care (clinic, level 1 hospital, level 2 hospital, level 3 hospital) was assigned to each based on predetermined classifications of gynaecological conditions into their most suitable levels of care. Results One hundred and ninety three (96.5%) of the participants were referred, and seven (3.5%) were brought by paramedics in ambulances. The most common reason for referral was lower abdominal pain and or vaginal bleeding in pregnancy (n=60; 30%), and the majority of these patients were treated for miscarriages (n=34; 57%). Twenty-four (12%) required admission to hospital. The bulk of patients were classified as level 1 (n=89; 44.5%), with 51 (25.5%) being level 2 and 50 (25%) being level 3 patients. Ten (5.0%) were considered to be primary healthcare (clinic) patients based on their gynaecological conditions. Conclusion The study found that the referral system around Soweto is in place and utilized appropriately and the majority of patients were referred. The study further found that CHBAH serves largely as a district hospital for the surrounding clinics. A fully functioning district hospital would likely relieve CHBAH of much of its burden of patients in the GOPD.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Obstetrics and Gynaecology Johannesburg, October 2015